Exploring the Prevalence and Correlates Associated With Intimate Partner Violence During Pregnancy in Bangladesh. Issue 1 (January 2021) - Islam, Md. Jahirul; Mazerolle, Paul; Broidy, Lisa; Baird, Kathleen
Intimate partner violence (IPV) during pregnancy is known to have multiple detrimental consequences for the woman and potentially for her unborn child. However, little is known about the nature and extent of IPV during pregnancy, particularly in developing countries, which compromises efforts to address the problem. Relying on population-based data, this article examines the extent, patterns, and correlates associated with physical, sexual, and psychological IPV during pregnancy in Bangladesh. Cross-sectional survey data were collected between October 2015 and January 2016 from 426 new mothers, aged 15 to 49 years, who were in the first 6 months postpartum. IPV was assessed with a validated set of survey items. Multivariate logistic regression analyses were conducted to evaluate correlates associated with different types of IPV. Overall, 66.4% of women experienced any IPV during pregnancy. The prevalence of physical, sexual, and psychological IPV was 35.2%, 18.5%, and 65%, respectively. These forms of IPV often overlap, particularly physical and psychological IPV. Pregnant women who report limited social support and have controlling husbands are at significantly increased risk for all three types of IPV during pregnancy. Women who cling to traditional gender roles and those with low self-esteem exhibit increased risk for physical and psychological IPV during pregnancy. Psychological IPV during pregnancy is also correlated with low decision-making autonomy and childhood exposure to violence. Women whose husband's demand a dowry at marriage are at increased risk of sexual IPV during pregnancy. Results reinforce the need to conduct routine screening during pregnancy to identify women with a history of IPV and to be able to offer help and support. The findings also reinforce calls for gender equity and women's equal access to family and social resources thereby increasing women's social support networks, their self-esteem, and autonomy, and reducing their risk of IPV during pregnancy.